Combined repetitive transcranial magnetic stimulation and medication treatment for depression is associated with serum amyloid a level: Evidence from naturalistic clinical practice - Xu, You; Han, Li; Wei, Youdan; Mao, Hongjing; Yu, Zhenghe (Frontiers in Neuroscience, 2022)
Objective Repetitive transcranial magnetic stimulation (rTMS) has a positive effect on patients with depressive disorder, while the underpinning molecular mechanism is unknown. Here, we aimed to investigate the effect of rTMS on serum levels of serum amyloid A (SAA) and testosterone in a real-world setting. Materials and methods In total, ninety-seven patients with depressive disorder were treated with medicine and rTMS (the rTMS group) while 122 patients were treated using the medicine only (the control group). Plasma levels of SAA (n = 52) and testosterone (n = 37) were measured before and after 2 weeks of treatment, and the treatment effect was evaluated by Hamilton Rating Scale for Depression (HAMD). Results The treatment effect revealed by the percentage of decrease in HAMD in the second week was significantly greater in the rTMS group compared with the control group. No significant difference was found in SAA or testosterone levels between the two groups. However, the percentage of changes in SAA (r = −0.492, p = 0.017) in the second week was significantly correlated with the percentage of decrease in HAMD score in the rTMS group, but not in the control group. Conclusion Patients with depression benefit more from combined rTMS and medication treatment in this naturalistic study. Changes in SAA level, but not testosterone level, were related to depressive remission after 2 weeks’ combined treatment.